(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This article analyzes a set of interviews with Mapuche poets proposing a metadiscursive articulation between the literary field (poetry) and the journalistic field (interview). The corpus analisys`s suggest the existence of three tension in poetic practice that can be seen in interviews with the authors. These tensions are manifested in three fundamental binomials that function here as categories of analysis: high-low culture; public-private distinction and dynamic articulation between identity-alterity. Finally, an intercultural dimension it is proposes as an articulating pivot of categories previously implemented and analyzed in Mapuche poetry.